FORMULATION AND EVALUATION OF METFORMIN HYDROCHLORIDE AND GLICLAZIDE SUSTAINED RELEASE BILAYER TABLETS: A COMBINATION THERAPY IN MANAGEMENT OF DIABETES - ALETI, RAJESWARI; BARATAM, SRINIVASA RAO; JAGIRAPU, BANGARUTHALLI; KUDAMALA, SRAVYA (International Journal of Applied Pharmaceutics, 2021)
Objective: The main objective of the present investigation is to develop a sustained-release (SR) formulation to optimize the postprandial elevation of glucose level in type 2 Diabetic subjects using combination therapy. In the present research work, bilayer sustained release formulation of metformin hydrochloride (MFH) and gliclazide (GLZ), based on monolithic-matrix technology was developed and evaluated. Methods: The formulations of metformin hydrochloride layer and gliclazide layer that contain polyox WSR coagulant and different viscosity grades of hydroxyl propyl methylcellulose (HPMC) as sustained-release matrix were prepared by direct compression and wet granulation method respectively. The bilayer tablets were prepared after carrying out the optimization of metformin layer and evaluated for various pre-compression and post-compression parameters. For the best formulation selected on basis of in vitro evaluation of tablets, Fourier-transform infrared spectroscopy (FT-IR) studies and comparison of in vitro dissolution profile of developed formulation with the innovator were performed. Results: Metformin hydrochloride and gliclazide showed sustained release of drug by diffusion mechanism and followed first-order kinetics. The best formulation of metformin hydrochloride (M7) and gliclazide (G8) show 99.93% and 99.65% of drug release in 24 h respectively. The similarity factor (f2) was 79.95 for metformin hydrochloride and 73.62 for gliclazide when compared with the innovator. Conclusion: The monolith diffusion-controlled bilayer tablets of metformin hydrochloride and gliclazide offer improved patient compliance and convenience with better postprandial hyperglycemic control with once-a-day dosing. The sustained release of the drug up to 24 h regulate antidiabetic activity round the clock with minimal side effects.